Design and Control of a Seaweed Dryer Prototype using a Hybrid Power Source - setiyono, setiyono; Syahrul, Elfitrin; Nur’ainingsih, Dyah (Vokasi Unesa Bulletin of Engineering, Technology and Applied Science, 2026)
This study presents the design and control of a seaweed dryer prototype powered by a hybrid energy source combining wind and photovoltaic (PV) systems. The prototype is developed to improve the efficiency and sustainability of seaweed drying processes in coastal and remote areas with limited grid access. The control system integrates several sensors and switch modules to enhance automation and operational reliability. A Low Voltage Disconnect (XH-M609) module is employed to protect the battery system by disconnecting the load when voltage drops below a safe threshold. A photocell sensor is used to detect sunlight intensity, allowing the system to operate the dryer only during adequate daylight, thereby conserving energy. Additionally, a rain drop sensor is integrated to pause the drying process during rainfall to prevent rehydration of the seaweed. A relay module is used to control the switching of dryer components based on real-time sensor feedback. The entire system is designed for both automatic and manual modes, ensuring flexibility for user intervention when necessary. Simulation and field test results show that the prototype can effectively utilize hybrid renewable energy sources while maintaining protection and adaptive control based on environmental conditions, offering a cost-efficient and eco-friendly solution for small-scale seaweed farmers